Platelet-rich fibrin, "a faster healing aid" in the treatment of combined lesions: A report of two cases - Parupalli Karunakar; Jammula Surya Prasanna; Matapathi Jayadev; Guniganti Sushma Shravani (Wolters Kluwer Medknow Publications, 2014)
Anatomically the pulp and periodontium are connected through apical foramen, and the lateral, accessory, and furcal canals. Diseases of one tissue may affect the other. In the present case report with two cases, a primary periodontal lesion with secondary endodontic involvement is described. In both cases, root canal treatment was done followed by periodontal therapy with the use of platelet-rich fibrin (PRF) as the regenerative material of choice. PRF has been a breakthrough in the stimulation and acceleration of tissue healing. It is used to achieve faster healing of the intrabony defects. Absence of an intraradicular lesion, pain, and swelling, along with tooth stability and adequate radiographic bone fill at 9 months of follow-up indicated a successful outcome.